2021
DOI: 10.1101/2021.03.22.436366
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide screen identifies curli amyloid fibril as a bacterial component promoting host neurodegeneration

Abstract: Growing evidence indicate that gut microbiota play a critical role in regulating the progression of neurodegenerative diseases, such as Parkinson's disease (PD). The molecular mechanism underlying such microbe-host interaction is unclear. In this study, by feeding C. elegans expressing human α-syn with E. coli knockout mutants, we conducted a genome-wide screen to identify bacterial genes that promote host neurodegeneration. The screen yielded 38 genes that fall into several genetic pathways, including curli f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…In another genetic model of PD (Pink1 -/-), intestinal infection with Gram-negative bacterial pathogens was shown to elicit an immune reaction that leads to neuronal degeneration and motor deficits, and which can be reversed with the PDmedication, L-dopa 13 . In addition, we and others have found that, curli, an amyloidogenic protein produced by Gram-negative Escherichia coli, induces alpha-synuclein aggregation and accelerates disease in the gut and neurodegeneration in the brain [14][15][16] . We have detected overabundance of opportunistic pathogens in the gut microbiomes of individuals with PD 17 .…”
mentioning
confidence: 84%
“…In another genetic model of PD (Pink1 -/-), intestinal infection with Gram-negative bacterial pathogens was shown to elicit an immune reaction that leads to neuronal degeneration and motor deficits, and which can be reversed with the PDmedication, L-dopa 13 . In addition, we and others have found that, curli, an amyloidogenic protein produced by Gram-negative Escherichia coli, induces alpha-synuclein aggregation and accelerates disease in the gut and neurodegeneration in the brain [14][15][16] . We have detected overabundance of opportunistic pathogens in the gut microbiomes of individuals with PD 17 .…”
mentioning
confidence: 84%
“…In another genetic model of PD (Pink1 -/-), intestinal infection with Gram-negative bacterial pathogens was shown to elicit an immune reaction that leads to neuronal degeneration and motor deficits, and which can be reversed with the PD-medication, L-DOPA 16 . In addition, we and others have found that, curli, an amyloidogenic protein produced by Gram-negative Escherichia coli, induces alpha-synuclein aggregation and accelerates disease in the gut and neurodegeneration in the brain [17][18][19] . We have detected overabundance of opportunistic pathogens in the gut microbiomes of individuals with PD 20 .…”
Section: Introductionmentioning
confidence: 84%
“…The bacterial-derived amyloidogenic protein, curli, exacerbates alpha-synuclein pathology and inflammation in experimental models of PD [17][18][19] . Many Enterobacteriaceae species encode curli 56 .…”
Section: Bacterial Amyloid Curlimentioning
confidence: 99%
“…C. elegans is an attractive model to study neurodegenerative diseases because of its distinctive attributes, such as the well-characterized genetic toolsets and the mapping of the organism's entire neural wiring of the organism (11). Moreover, studies in C. elegans have demonstrated the role of pathogens in inducing neural changes considered hallmarks of neurodegeneration (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%